URGENSI PERAN PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN DALAM PENEGAKKAN HUKUM TINDAK PIDANA PENCUCIAN UANG - Ida Rahma (Jurnal Hukum Samudra Keadilan, 2022)
Economic crimes attract enough these days. Types of crimes that damage the joints of the economic life of the nation is increasingly flour is handenrich the world participate. Crime of money laundering is one of the new dimension of economic crimes. Money laundering is the process done to change the out come of crimes such as corruption, narcotics, gambling, smuggling, and other serious crimes, with theuse of banking services for money derived from criminal acts with the intent to conceal the origin of money. Concerning combating money laundering in Indonesia is regulated by Law No.8 of 2010 on the Prevention and Combating of Money Laundering which replaces, Act No.15 of 2002 as amended by Act No. 25 of 2003. Regulation of money laundering has been quite effective in both anticipate and combat money laundering by means of tracing the flow of funds in the banking institutions associated with the disclosure of crime confiscated at the same time also criminalize any one who receives the flow of crime.